An Audit of Surgical Management of Pressure Sores in a Resource Constrained Hospital in Kenya. (20th June 2013) - Nangole, W. F.; Khainga, S. O.; Otieno, Soren; Tanga, Audi
Abstract : Objective . To determine the surgical management of pressure sores at the National Spinal Injury Hospital and the outcome. Design . This was a four-year prospective study from June 2008 to June 2012. Setting . The study was carried out at the National Spinal Injury Hospital, Nairobi, Kenya. Subjects . Patients with pressure sores operated on during the defined period of study. Results . A total of 46 patients with 58 pressure sores were operated on during the defined period of study. The male : female ratio was 10.5 : 1. The mean age was 36.5 years. Trochanteric sores accounted for 60 percent of the pressure sores operated on with the V-Y tensor fascia lata, the commonest surgical procedure, accounting for 37 percent of the procedures performed. At one year of followup 90 percent of the surgeries done were successful with no ulcer recurrence noted. Conclusion . Surgical management of pressure sores even in resource constrained environment would result in faster rehabilitation and early patient discharge. The recurrence of the pressure sores could be greatly reduced by involving patients relatives in the rehabilitation and home-based care.